Diagnóstico ambiental do rio corumbataí em trecho urbano do município de rio claro, SP - Frederice, Aline [UNESP]; do Amaral, Daniel Calderaro [UNESP]; Moreira, Danielle Coimbra [UNESP]; Shitara, Julia [UNESP]; Fuess, Lucas Tadeu [UNESP]; Costa, Natália Rezende [UNESP]; Curan, Roberta Moraes [UNESP]; Reis, Fábio Augusto Gomes Vieira [UNESP]; do Carmo Giordano, Lucilia (My University, 2010)
The environmental analysis is an important tool used in forecasting and mitigation of environmental problems. Focusing on the occupation of marginal areas of the Corumbataí River in an urban stretch in the city of Rio Claro (SP), this study aimed to gather information on situations of risk, both to the environment and the population, verified in that area. Through field observation and in specific studies, the geological and geotechnical aspects, the characteristics of surface waters and aspects of urbanization were analyzed. The results show that the environmental problems diagnosed are related to lack of planning in the occupation of the area. Moreover, the natural characteristics of the physical environment expose people to risks such as floods and soil slides.

O diagnóstico ambiental é uma importante ferramenta utilizada na previsão e na mitigação de problemas ambientais. Tendo como foco a ocupação de áreas marginais do Rio Corumbataí em um trecho urbano do município de Rio Claro (SP), o presente trabalho buscou reunir informações referentes às situações de riscos, tanto ao ambiente quanto à população, verificadas na área. Por meio da observação em campo e de estudos específicos, foram realizadas análises referentes aos aspectos geológico-geotécnicos e às características das águas superficiais e da urbanização na região. Os resultados demonstram que os problemas ambientais diagnosticados estão relacionados à falta de planejamento na ocupação da área. Além disso, as características naturais do meio físico expõem a população a riscos, como inundações e escorregamentos de solo. Palavras-chave: diagnóstico ambiental, problemas ambientais, aspectos geológico-geotécnicos, estudo hidrológico, ocupação urbana.
Environmental analysis of the Corumbataí river in an urban stretch in the city of Rio Claro, SP
Keywords: Environmental analysis; Environmental problems; Geological and geotechnical aspects; Hydrological study; Urban occupation; environmental stress; flood; hydrological regime; risk assessment; river water; sliding; surface water; urban site; urbanization; Brazil; Corumbatai River; Rio Claro; Sao Paulo [Brazil]